(3JMQjQ EbdjOSs - (3GdMSf Hf SajGf Hf YGeQ GdTjHGfqj GdnqfnShj, CHh GdYHGS,J (B303 (3g` s ((3CMeO Hf eMeO Hf SfGf GdQTfSi s)
(3ChdgG (B:s
(3hHYO, abO ChVM GdYdeGA ef GdChGFd GdbOQ GdPi jMJGL Edjg GdEfSGf ef cd Yde Cf jJUhQg hjMbbg s
(3BNQgG (B:s
(3hEYJeGOkG Ydi eGbQQfGg ai cJGH (B"(3GdHdGZ(B" (3GdPi UfafGg ai TQM cJGH (B"(3ChbdjOS(B" (3ai GdCUhd s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3LeY s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdQjGVjGJs